Impact of Family Burden: A Case Study Re-pasung of People with Mental Illness - Rahma Yulis; Hardianti Hardianti; Rasmawati Rasmawati (Universitas STRADA Indonesia, 2021)
The burden faced by families in caring for family members with mental illness is one important indicator in re-pasung actions. The purpose of this study was to describe the burden of the family in caring for people with mental illness post pasung which causes re-pasung. Qualitative design with a multiple instrumental case study approach using two cases chosen to provide an understanding of the re-pasung case. Six people participated in this study who were selected through a purposive sampling method. The data collection was carried out by in-depth interviews with the case subject's family. Four categories were produced in this study, namely alternative therapy as an initial step in handling mental illness, pasung as a crisis management strategy, release of pasung and treatment in hospital, and re-pasung as a result of burden on the family. Subjective and objective burdens that can not be handled are predictors of re-pasung.